2016
DOI: 10.1111/jai.13016
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships and basic biological information on 64 fish species from lower sections of the Wujiang River, China

Abstract: Summary The present study provides the length–weight relationships (LWRs) for 64 fish species belonging to eight families from the lower sections of Wujiang River, a tributary of the upper Yangtze River in China. LWRs for eight of these species are unknown to FishBase and new maximum body weights are recorded for 25 species. In addition, some basic biological information on 64 fish species is also summarized. These results will be useful for fishery research, management and conservation in the Wujiang River.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
4

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
3
11
4
Order By: Relevance
“…Two species also had marked differences in b values compared with records in FishBase and other studies. The b value (3.054) of L. rubrilabr in the present study was higher than (2.88) in specimens from the Wujiang River basin (Yang et al., ), the reason perhaps being that the size range covered by Yang et al. () was somewhat broader (7.7–19.2 cm SL) than in the present paper (5.5 cm).…”
Section: Discussioncontrasting
confidence: 75%
“…Two species also had marked differences in b values compared with records in FishBase and other studies. The b value (3.054) of L. rubrilabr in the present study was higher than (2.88) in specimens from the Wujiang River basin (Yang et al., ), the reason perhaps being that the size range covered by Yang et al. () was somewhat broader (7.7–19.2 cm SL) than in the present paper (5.5 cm).…”
Section: Discussioncontrasting
confidence: 75%
“…Comparing the obtained b values with those of previous studies (Cao, Yang, Cai, & Pan, 2016;Chen et al, 2016;Duan et al, 2015;Lei, Liang, Sui, & Chen, 2015;Que et al, 2015;Yang et al, 2016) value represents the body form of fish (Froese, Thorson, & Reyes, 2014), and is affected by a number of factors such as gonad maturity, sex, diet, stomach fullness, health, age, fishing time as well as the area and fishing vessels (Sani et al, 2010). However, these factors were not considered in the present study.…”
Section: Discussionmentioning
confidence: 73%
“…In this study, in spite of the LWRs of the two species were not found in the FishBase (Froese & Pauly, ), the values of parameter b remained within the expected range of 2.5–3.5 for all species (Froese, ). Compared with previous studies, differences in LWRs of fishes can be attributed to many factors, such as the differences of sample size, fishing time, fishing gears, sampling methodology, gonad maturity, geographical range, sex, diet and stomach fullness (Bonilla‐Gómez, Robles, & Vega, ; Franklin, Brong, Dow, & Craig, ; Froese, ; Que et al, ; Sani et al, ; Yang et al, ). Unfortunately, the sampling also lacks uniform standards and the same conditions, which are not taken into account.…”
Section: Discussionmentioning
confidence: 80%